Empowering Visual Communication Design Students to Support Tourism Village through Entrepreneurship Education - Ayyub Anshari Sukmaraga; Andreas Syah Pahlevi; Fariza Wahyu Arizal; Ima Kusumawati Hidayat; Khairul Azhar bin Mat Daud (International Research-Based Education Journal, 2025)
This study investigates the effectiveness of integrating Entrepreneurship Education into Visual Communication Design (VCD) curricula to enhance students' empathy and their capacity to support community development. By embedding entrepreneurial principles, the program aims to cultivate social responsibility and practical skills, empowering students to contribute to the economic and cultural sustainability of local communities. The research involved two student cohorts from Universitas Negeri Malang and Universitas Ma Chung, who collaborated with Kampung Warna-Warni, a renowned tourism village in Malang, Indonesia. Over a one semester workshop, students designed souvenirs to boost creativity and income for village residents while fostering their own empathy. Result show a the potential of combining academic learning with practical application to achieve both educational and community development objectives.